Supply Chain Management and Logistics in Latin America : A Multi-Country Perspective. - Yoshizaki, Hugo Tsugunobu Yoshida. (Emerald Publishing Limited, 2018)
Latin America is a fast-growing market, but its poor infrastructure, explosive urbanization, expensive and inefficient logistics, and multiple social problems continue to pose major problems to logistics professionals and academics. Here leading scholars across Brazil, Colombia, Cuba, Ecuador, Peru, Panama, and the USA address these issues.